Firenze e Dubrovnik all'epoca di Marino Darsa (1508-1567) Atti della Giornata di studi Firenze, 31 Gennaio 2009 - PINELLI, PAOLA (Biblioteca di Studi Slavistici, 2010)
This book contains the proceedings of the study day devoted to "Firenze e Dubrovnik all'epoca di Marino Darsa (1508-1567)"which was held in Florence on 31 January 2009. In addition to exploring the work of the playwright and the subjects he addressed, the contributions also map out the cultural and economic context of his work, dwelling in particular on the influence and importance that the relations between Tuscany, and Florence in particular, and Dubrovnik (Ragusa) had upon his production. Enhanced by a short biography of Marin Držić and a selection of critical articles, the publication is addressed to scholars while also being proposed as a tool for teaching on university courses, providing an initial introduction to the man and his work, undeservedly little known, set against the political and economic background of his time.